Nuclear posttranscriptional processing of thymidine kinase mRNA at the onset of DNA synthesis. - Gudas, J M (1988)
The posttranscriptional regulatory mechanism(s) underlying thymidine kinase (TK) mRNA accumulation was investigated in BALB/c 3T3 cells during their progression from G0 into S phase of the cell cycle. Very little TK mRNA could be detected in either the nuclear or the cytoplasmic compartment from cells harvested in G0 or G1. At the onset of S phase, however, the level of nuclear TK mRNA precursors and mature TK mRNAs increased dramatically. The high molecular weight TK heterogeneous nuclear RNA species detected in the nuclei of S-phase cells were polyadenylylated and hybridized to intron sequences derived from the TK gene. A series of high molecular weight precursors could be chased to lower molecular weight species in the presence of actinomycin D, suggesting an ordered removal of intron sequences with the kinetics of a precursor-product relationship. These results demonstrate a striking change in the nuclear posttranscriptional processing of TK heterogeneous nuclear RNA at the G1-S boundary and, furthermore, define a model system for the examination of RNA-processing events in vivo.